Hieromonk Athanasius`s (Nechaev) letters to hieroschemamonk Ephraim (Khrobostov) from Paris to Valaam (1927–1929) - Tatyana Shevchenko (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
Letters from Hieromonk Athanasius (Nechaev) to his confessor and elder, Hieroschemamonk Ephraim (Khrobostov) are presented in the publication. They were written from Paris to Valaam in Finland, where at that time the Valaam Monastery was located. Hieromonk Athanasius - the future archimandrite and spiritual mentor of monasticism abroad, the superior of the Three Hierarchs metochion in Paris (1933-1943), dean of the parishes of the Moscow Patriarchate in France, the first spiritual mentor of the future Metropolitan Anthony of Sourozh (Bloom). His addressee was the fraternal confessor at the Valaam Monastery, and before the revolution, the confessor of Grand Duke Nikolai Nikolayevich (the younger) and his family, Hieroschemamonk Ephraim (Khrobostov), - is the respected and authoritative member of the spiritual governing body of the monastery. In the Smolensk skete on Valaam, he daily served a liturgy in memory of the Russian soldiers who died at the front for the faith, the Tsar and the Fatherland. The letters were written during the period of study of Father Athanasius at the St. Sergius Theological Institute in Paris and during his service in the monastery-orphanage "Unexpected Joy" in Livry-Gargan near Paris. They deal with many problems of the church life of the Russian diaspora in France and the Russian emigration in general as a phenomenon. Father Athanasius described the causes of jurisdictional disputes in exile, problems at the Theological Institute, conflicts between hierarchs, and more. He was something of a correspondent who kept the Valaam monastery authorities up to date on events. Describing in detail the essence of the disagreements, at some point he apparently got tired of them and plunged headlong into pastoral work, warmly describing the life of the emigrant communities he served. During the cross-over of Metropolitan Evlogy to the Patriarchate of Constantinople, Father Athanasius could not reconcile himself to the break with the Russian Church, and believed that it was better to return to Valaam. However, these plans were not destined to come true.